Implications of pesticide use regulation on soil sustainability in Uganda - Yahyah, Hadijah; Kameri-Mbote, Patricia; Kibugi, Robert (Elsevier Ltd, 2024)
Reducing pesticide use has become a goal shared by several countries, Uganda inclusive and a major issue in public policies since the adverse impacts of pesticides on environmental media such as soil and on human health have been clearly demonstrated. The main environmental concerns related to pesticides are soil, water pollution and damage to non-target organisms including plants, birds, wildlife, fish and crops. On one hand, pesticides can control pests and diseases, and increase agricultural productivity, which is essential for food security and economic development. However, the positive effects have proven to be short-lived. Moreover, the indiscriminate and injudicious use of pesticides without proper regulation and awareness, more so by small-scale farmers, can lead to detrimental effects on soil health and long-term sustainability. The challenge is exacerbated by pesticides that can persist in the environment and accumulate in the soil over time, leading to soil degradation. Accordingly, regulation of pesticide use then becomes more critical if the adverse effects of pesticide use are to be mitigated. Indeed, Uganda recognizes the importance of sustainable agricultural practices and the need to regulate pesticide use to protect soil health and ensure long-term agricultural productivity. This is manifested in the existing regulatory framework on pesticide use, although challenges and threats to soil sustainability still abound especially from the highly fragmented and sectoral-based approaches. This paper examines the implications of pesticide use regulation on soil sustainability in Uganda, a country heavily reliant on agriculture for food security and economic growth. Suggestions are proffered on some interventions that align with soil sustainability.